A Critical Appraisal of Integrated Treatments of Contingency Findings - Moberg, Dennis J.; Koch, James L. (Academy of Management Journal, 1975)
A number of questions are raised about the theoretical nature of aggregative models of situational approaches to organization and management. These include questions regarding the domain of contingency views, the laws of interaction specified by these models, and the applicability of integrated contingency viewpoints.